2018
DOI: 10.3390/ijms19103120
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic Astragalin Galactoside Induces T Helper Type 1-Mediated Immune Responses via Dendritic Cells

Abstract: A flavonoid Astragalin (kaempferol-3-O-β-d-glucopyranoside, Ast) has several biological activities including anti-oxidant, anti-HIV, and anti-allergic effects. Nonetheless, its insolubility in hydrophilic solvents imposes restrictions on its therapeutic applications. In this study, we investigated the effects of water-soluble astragalin-galactoside (kaempferol-3-O-β-d-isomaltotrioside, Ast-Gal) on murine bone marrow-derived dendritic cell (DC) maturation and T helper (Th) cell-mediated immune responses. Ast-Ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Astragalin dapat menurunkan respon inflamasi yang diinduksi lipopolisakarida (LPS) dengan menekan jalur persinyalan NF-кB (Riaz et al, 2018;Shukla et al, 2019). Senyawa astragalin galaktosidase dilaporkan lebih aktif daripada astragalin dalam proses maturasi sel dendritik untuk meningkatkan respon imun yang dimediasi oleh sel helper TH1 (Jeon et al, 2018). (5) Niruriflavon, merupakan flavonon yang memiliki aktivitas farmakologi sebagai hepatoprotektor dengan mekanisme menangkal radikal bebas yang berperan dalam proses hepatotoksik (Bagalkotkar et al, 2006;Kaur et al, 2017).…”
Section: Flavonoidunclassified
“…Astragalin dapat menurunkan respon inflamasi yang diinduksi lipopolisakarida (LPS) dengan menekan jalur persinyalan NF-кB (Riaz et al, 2018;Shukla et al, 2019). Senyawa astragalin galaktosidase dilaporkan lebih aktif daripada astragalin dalam proses maturasi sel dendritik untuk meningkatkan respon imun yang dimediasi oleh sel helper TH1 (Jeon et al, 2018). (5) Niruriflavon, merupakan flavonon yang memiliki aktivitas farmakologi sebagai hepatoprotektor dengan mekanisme menangkal radikal bebas yang berperan dalam proses hepatotoksik (Bagalkotkar et al, 2006;Kaur et al, 2017).…”
Section: Flavonoidunclassified
“…Both BMP2/4 and TGFβ are upregulated by DLE and are molecules related to the immune system. Myricetin, quercetin, and kaempferol exert anti-inflammatory and modulatory effects on various types of immune cells [ 24 , 25 ]. Bone marrow has various immune cells, and T cells are a source of BMP2/4 and TGFβ.…”
Section: Resultsmentioning
confidence: 99%
“…Many previous studies have proved that kaempferol has good anti-inflammatory, immune regulation, antioxidation, antitumor, and other pharmacological properties [ 20 ]. It has been shown that kaempferol can induce Th1-mediated immune responses through dendritic cells [ 24 ]. Kaempferol can also exhibit antioxidant activities by increasing the expression of related antioxidant enzymes and reducing oxidative stress [ 25 ].…”
Section: Discussionmentioning
confidence: 99%